Military Medicine in American Samoa—Connecting With Indo-Pacific Partners. Issue 3 (31st July 2021) - Pierce, Bradley T; Pucci, Josephine U; Rich, Elizabeth L; Ottolini, Martin; Schramm, Jill F; DeLeon, Patrick H; Hussey, Sean; Tripoli, Louis C; Chung, Kevin K
ABSTRACT: With the rise of great power competition in the Indo-Pacific, Global Health Engagement can facilitate positive foreign relations. Increasing military medical outreach in American Samoa will provide improved health care in the territory, offer relevant medical training in resource-limited environments, and build connections with a community that has many uniformed members.